The Effects of Motivation, Leadership, and Work Environment on Employee's Performance: A Case of Local Government Agency in Emerging Country - Shantini Rumbi; Ferdinandus Christian; Suparti (Britain International for Academic Research (BIAR) Publisher, 2021)
The performance of the Yapen Island Regency's Agriculture and Food Security Agency, as the responsible local government agency in developing the local agriculture sector, is still far from optimal, as seen from the decrease in its budget absorption. This study aims to determine and analyze the influences of work motivation, leadership, and work environment on employee performance at the mentioned local government agency. This quantitative research used a survey employing a questionnaire as a research instrument. Of 108 public officers became the sample. Multiple regression tests analyzed data with the help of SPSS software. The results showed that 1) there was a significant influence of motivation on employee performance, 2) there was a significant effect of leadership on employee performance, 3) there was a significant effect of the work environment on employee performance, and 4) motivation was the most dominant factor in affecting employee performance at the observed local government agency.